Optogenetic stimulation of kisspeptin neurones within the posterodorsal medial amygdala increases luteinising hormone pulse frequency in female mice. (11th February 2020) - Lass, Geffen; Li, Xiao Feng; de Burgh, Ross A.; He, Wen; Kang, Yanping; Hwa‐Yeo, Shel; Sinnett‐Smith, Lydia C.; Manchishi, Stephen M.; Colledge, William H.; Lightman, Stafford Louis; O'Byrne, Kevin T.
Abstract: Kisspeptin within the arcuate nucleus of the hypothalamus is a critical neuropeptide in the regulation of reproduction. Together with neurokinin B and dynorphin A, arcuate kisspeptin provides the oscillatory activity that drives the pulsatile secretion of gonadotrophin‐releasing hormone (GnRH), and therefore luteinising hormone (LH) pulses, and is considered to be a central component of the GnRH pulse generator. It is well established that the amygdala also exerts an influence over gonadotrophic hormone secretion and reproductive physiology. The discovery of kisspeptin and its receptor within the posterodorsal medial amygdala (MePD) and our recent finding showing that intra‐MePD administration of kisspeptin or a kisspeptin receptor antagonist results in increased LH secretion and decreased LH pulse frequency, respectively, suggests an important role for amygdala kisspeptin signalling in the regulation of the GnRH pulse generator. To further investigate the function of amygdala kisspeptin, the present study used an optogenetic approach to selectively stimulate MePD kisspeptin neurones and examine the effect on pulsatile LH secretion. MePD kisspeptin neurones in conscious Kiss1‐Cre mice were virally infected to express the channelrhodopsin 2 protein and selectively stimulated by light via a chronically implanted fibre optic cannula. Continuous stimulation using 5 Hz resulted in an increased LH pulse frequency, which was not observed at the lower stimulation frequencies of 0.5 and 2 Hz. In wild‐type animals, continuous stimulation at 5 Hz did not affect LH pulse frequency. These results demonstrate that selective activation of MePD Kiss1 neurones can modulate hypothalamic GnRH pulse generator frequency.